Memahami Aliran Khawarij, Qadariah, dan Jabariah - Siti Nurzana; Paisal Ipanda Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to see how history emerged, the main teachings and figures of the Kalam science school, namely: Khawarij, Qdariah and Jabariah. These three schools are schools that emerged in Islam and have different teaching principles. The method in this research is library research by collecting research data from literature and using the world of texts as the main material for analysis. Other relevant sources can also support and enrich the data needed using books by Islamic scholars. The results of this research show that the emergence of the khawarij was as people who left Ali's ranks, where the initial emergence of the khawarij was due to political events, namely the appointment of the Caliph. The main teachings of the khawarij were to disbelieve those who accepted the tahkim event. Furthermore, the teachings of the sect, while the Qdariah and Jabariah schools initially emerged due to the problem of divine destiny, the first understanding, namely the Qdariah understanding, they argue that humans can determine actions, while the Jabariah believes that in essence humans do not have a will, but are only forced to do so.